Optimizing forest management in the face of bark beetle risk - Romeiro, Joyce M.N.; Strîmbu, Victor F.; Eid, Tron; Kangas, Annika (Elsevier, 2025)
The rising impact of the spruce bark beetle (Ips typographus L.) on Europe's forests is becoming a major concern, with climate change intensifying the problem. This situation has sparked discussion across Europe about adopting new, adaptive forest management strategies to mitigate the economic impacts on the forestry sector. Despite this, some regions have yet to fully embrace long-term strategies against bark beetle outbreaks from a climate change perspective. In our study, we examined the effects of integrating bark beetle risk into forest management strategies, considering both current and future climate change scenarios. Our findings indicate that reducing rotation length of low density stands with a high proportion of Norway Spruce situated in more productive sites yields substantial economic advantages. Particularly, regions with a history of bark beetle outbreaks, like Vestfold in Norway, stand to gain significantly from early harvesting. The economic gain from harvesting earlier in this region is projected to increase nearly tenfold over the next 50 years under climate change scenarios. Additionally, we recommend considering the use of mixed tree species within forests as another adaptation strategy, to enhance forest resilience against bark beetle infestations and other natural disturbances.
Keywords: climate change; forest management; disturbance management; Ips typographus; Picea abies